Pengaruh Likuiditas Terhadap Kinerja Perusahaan Pada Perusahaan Yang Terdaftar Di BEI - Nabilla Octaviana Dirmansyah; Lala Syalsabila; Henny Setyo Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this research is to conclude the impact of liquidity on firm performance. The sample in this study are companies from the food and beverages subsector listed on Indonesia Stock Exchange in 2016-2020. The sampling technique used in this study is purposive sampling and the analysis method is panel data regression. The independent variables in this study are acid ratio and current ratio, and the control variable is sales growth and firm size, with firm performance as the dependent variable. The results show that the Acid ratio has an insignificant effect on ROA and ROE, the Current Ratio has an insignificant effect on ROA and has a negative and significant effect on ROE. Sales growth has a positive and significant effect on ROA and has an insignificant effect on ROE. Firm size has a positive and significant effect on ROA and ROE.